H3K4me3 CUT&Tag and Transcriptome Analysis Reveal the Epigenetic Regulatory Landscape in Gill Tissue of Large Yellow Croaker (Larimichthys crocea) Under Low Salinity Stress - Yang, Jian; Liu, Minhai; Shen, Weiliang; Zhou, Tingting; Wu, Xiongfei; Li, Qi; Lin, Zhihua (Frontiers in Marine Science, 2022)
H3K4me3 is an important histone modification that could influence DNA replication and RNA translation in response to abiotic stress. Here, RNA-seq analyses were conducted in gill tissues of large yellow croaker to identify the function of H3K4me3 under low salinity stress. Additionally, CUT&Tag analyses were performed to identify the genome-wide dynamic changes in H3K4me3 and explore the mechanisms by which H3K4me3 regulates gene expression. A total of 201 differentially expressed genes (DEGs) were identified between the 5‰ low salinity group (S-group) and 25‰ normal salinity group (C-group), among which 23 DEGs (11 up-regulated H3K4me3 targets and 12 down-regulated targets) were directly regulated by H3K4me3. Our findings thus describe the epigenetic regulatory landscape of H3K4me3 in gill of large yellow croaker during low salinity stress, and provide novel insights into the regulation mechanisms of H3K4me3 mediating the responses of aquatic animals to abiotic stress.